ダイ 29 ジ ナンキョク チイキ カンソク タイ ナツ タイ ホウコク 1987-1988 - 佐藤, 夏雄; サトウ, ナツオ; Sato, Natsuo (1990)
P(論文) 第29次南極地域観測隊は, 隊長渡辺興亜以下52名で編成された。このうち, 昭和基地の越冬隊は渡辺興亜越冬隊長以下27名, あすか観測拠点の越冬隊は矢内桂三越冬副隊長以下10名である。夏隊は, 佐藤夏雄夏隊長以下15名で編成され, 船舶技術者2名と報道関係者3名及び南極条約に基づく交換科学者として, 米国から1名および中国から2名が同行した。1987年11月14日, 東京湾を出港した「しらせ」は, オーストラリアのフリマントル港に寄港したのち, 12月17日, ブライド湾に到着し, 物資の輸送, あすか観測拠点における越冬態勢確立のための作業を実施した。12月30日, セールロンダーネ山地地学調査隊員を残し, ブライド湾を離れた「しらせ」は1988年1月2日に昭和基地に到着した。輸送(約700t), 大型アンテナ基礎工事や衛星受信棟などの建設作業, 野外調査などは1月31日までの間に終了し, 2月1日に越冬交代を行った。2月5日再びブライド湾に向かった。2月7日ブライド湾に到着し, セールロンダーネ山地地学調査隊の収容, 海底磁力計の揚収をした後, 海底地形観測等を実施した。2月14日から2月22日にかけてマラジョージナヤ基地, アムンゼン湾にて野外調査を実施した後, 今次隊から開始した東航(158°Eまで)及び北上中の海洋観測を行い, 3月20日シドニー湾に初寄港した。観測隊員は, 空路にて3月27日に, また「しらせ」は4月12日に東京湾に帰着した。 This report outlines the summer activities of the 29th Japanese Antarctic Research Expedition (JARE-29) in 1987-1988. The icebreaker SHIRASE, carrying 52 expedition members, 5 Japanese observers and 2 Chinese scientists led by Dr. O. WATANABE with cargo of about 900 t, left Tokyo on 14 November 1987. After calling at Fremantle in Western Australia, where an American scientist joined the party, the ship arrived at Breid Bay on 17 December. The helicopter and surface transportation of 160 t of cargo from the ship to Asuka Station was completed by 30 December. Two airplanes operated at Asuka Station by JARE-28 returned to the SHIRASE on 28 December. The ship reached Syowa Station on 2 January 1988,and the transportation of 730 t of cargo by means of helicopter and surface was completed by 12 January. After the accomplishment of constructing and fieldwork in the Syowa Station area, the SHIRASE left Syowa Station on 5 February and arrived again at Breid Bay on 7 February. The field party of the Sor Rondane Mountains was collected by her. On the way from Breid Bay to Sydney, Australia, the ship stopped over at Molodezhnaya Station and Amundsen Bay for a fieldwork. On 27 March, the members of expedition came back to the Tokyo Airport via Sydney, and the ship returned to the Tokyo Port on 12 April. The following scientific activities were carried out during the summer operation of ...